The Impact of Servant Leadership on Financial Performance and Green Performance: The Mediating Role of Organizational Commitment - Hendri Kwistianus; Like Gracia; Gabriela Clarence (Bina Nusantara University, 2025)
Despite the increasing interest in servant leadership studies and their relationship with green performance, limited research has examined the role of an organization's strategic management aspect. The research applied servant leadership theory to examine how servant leadership influences green and financial performance in Indonesia's manufacturing sector. The research uniquely emphasized organizational commitment as a mediating variable and provided empirical evidence to strengthen the theoretical linkage among these constructs, particularly in the manufacturing sector of Indonesia. The research method involved distributing an online questionnaire through Populix, with a total sample of 300 respondents consisting of employees at various levels who had been working for more than five years in manufacturing companies in Indonesia. Data analysis was conducted Using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of WarpPLS software to test each research hypothesis. The results indicate that servant leadership has a positive and significant influence on both green and financial performance. Additionally, organizational commitment partially mediates the relationship between servant leadership and two variables, strengthening the impact of servant leadership on green performance and financial performance in manufacturing companies in Indonesia. Manufacturing companies in Indonesia can adopt servant leadership to boost green performance through ethical decision-making and environmental responsibility. It enhances efficiency and innovation and reduces costs by empowering employees. The research contributes to the limited existing research that examines the relationship between servant leadership, financial performance, and green performance by exploring the mediating role of organizational commitment within the context of Indonesia’s manufacturing sector.